Is Digitalizaion Really Enchance SMEs Financial Performance? Empirical Evidence from Bangka Belitung - Ridwan, Muhammad Qomaruddin; Wardhani, Rulyanti Susi; Bahri, Alim; Altin, Darus; Karmawan, Karmawan; Imro'ah, Alfiany Alim (Ratio : Reviu Akuntansi Kontemporer Indonesia, 2026)
This study examines the impact of digitalization on the financial performance of small and medium-sized enterprises (SMEs) by comparing key performance indicators—Return on Assets (ROA), Return on Equity (ROE), Total Asset Turnover (TATO), and Profit Margin (PM)—before and after digital adoption. Using a sample of 275 SMEs, descriptive statistics and Wilcoxon tests (paired and one-sample) were employed to evaluate changes in financial outcomes. The results indicate significant improvements in ROA, ROE, and PM following digitalization, while TATO remained stable, suggesting that digitalization’s benefits are most immediate in profitability rather than operational efficiency. These findings reinforce the role of digital tools as strategic enablers of SME performance, emphasizing their contribution to cost management, financial transparency, and market expansion. The study offers practical recommendations for SMEs and policymakers to accelerate digital transformation and highlights avenues for future research, including sector-specific analysis, longitudinal studies, and cross-country comparisons.